2021
DOI: 10.3390/app11041469
|View full text |Cite
|
Sign up to set email alerts
|

Postural Stability and Proprioception Abnormalities in Patients with Knee Osteoarthritis

Abstract: Knee osteoarthritis (OA) leads to the damage of all joint components, with consequent proprioceptive impairment leading to a decline in balance and an increase in the risk of falls. This study was aimed at assessing postural stability and proprioception in patients with knee OA, and the relation between the impairment in postural stability and proprioception with the severity of OA and functional performance. Thirty-eight patients with knee OA were recruited. OA severity was classified with the Kellgren–Lawren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…This study's findings, which show substantial proprioceptive impairment in terms of increased JPE in the KOA group, are in accordance with findings from previously published papers that involve subjects with other types of knee condition [37,38]. Degenerative changes or atrophy that weaken muscles can damage joint structures, affect mechanoreceptors and proprioceptive afferent input to the higher centers, and compromise knee proprioception, which are a few potential causes of decreased proprioception in KOA patients [10,39,40]. Proprioception and the intricate afferent performance of the proprioceptive network system are affected by pain and edema in KOA patients [10,40].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study's findings, which show substantial proprioceptive impairment in terms of increased JPE in the KOA group, are in accordance with findings from previously published papers that involve subjects with other types of knee condition [37,38]. Degenerative changes or atrophy that weaken muscles can damage joint structures, affect mechanoreceptors and proprioceptive afferent input to the higher centers, and compromise knee proprioception, which are a few potential causes of decreased proprioception in KOA patients [10,39,40]. Proprioception and the intricate afferent performance of the proprioceptive network system are affected by pain and edema in KOA patients [10,40].…”
Section: Discussionsupporting
confidence: 91%
“…Alshahrani et al [10] showed that the magnitude of knee JPE was larger in individuals with KOA compared to asymptomatic groups in sitting positions (20° of flexion: d = 1.73, p < 0.001; 40° of flexion: d = 1.72, p < 0.001; 60° of flexion: d = 1.83, p < 0.001) and standing positions (20° of flexion: d = 1.89, p < 0.001). The mean knee JPE in our study ranged from 5.4° to 5.8°, which is the average error shown for KOA in different studies [10,11,[40][41][42].…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…In fact, in both groups, there was a significant quadriceps strength increase, and strength was significantly higher than that in the controls up to 12 months after surgery. This means that NMES can be used as a valid option when it is not possible to perform traditional strength training, as, for example, immediately postsurgery when the recovery of muscle strength may have positive effects for rehabilitation as a whole [20,21]. It has been reported that the early recovery of muscle strength following TKA is positively related to general functional outcome and performance [22].…”
Section: Figmentioning
confidence: 99%